Study Efisiensi Reproduksi Kambing Kacang dan Hasil Persilangannya Dengan Kambing Boer (Boerka) di Lombok - Ashari, M; Suhardiani, Agustien; Perwoto, Happy; Hidjaz, Tahyah; Andriati, Rina (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
This research was carried out with the aim of determining the reproductive efficiency of Kacang goats and goats resulting from crosses with Boer goats (Boerka goats). This research was carried out in the area of ​​development of the Kacang goat and a cross between the Kacang goat and the Boer goat (Boerka) in Lombok with the aim of determining the level of reproductive efficiency of the Boerka goat and the Kacang goat in the people's breeding business. The variables observed include: An Estrus Post Partum, Open Days, service per conception, service period and kid interval, litter size and first mating after giving birth. Location determination was carried out using purposive sampling based on the breed of goats being kept. Livestock samples were taken randomly from 60 mother goats (30 Kacang mother goats and 30 Boerka mother goats). The observation data was tabulated using the Excel program and then analyzed using the t-test. Data analysis activities use Genstat software. Goat race/breed has no significant effect (P > 0.05) on the first estrus after giving birth, service conception and number of offspring per birth, but has a significant effect (P < 0.05) on service period, days open and calving interval (kid interval). The calving interval for the mother Kacang goat is longer, namely 253.00 ± 14.87 days (8.4 months) compared to the mother Boerka goat, namely 234.86 ± 07.09 days (7.8 months).